One-step immunoassay of SARS-CoV-2 using screened Fv-antibodies and switching peptides - Jung, Jaeyong; Sung, Jeong Soo; Bong, Ji-Hong; Kim, Tae-Hun; Kwon, Soonil; Bae, Hyung Eun; Kang, Min-Jung; Jose, Joachim; Lee, Misu; Shin, Hyun-Jin; Pyun, Jae-Chul (Pergamon Press Ltd., 2024)
The Fv-antibodies were correponded to VH region of immunoglobulin G, which were composed of three complementarity determining regions (CDRs) for the specific binding of antigens. In this work, the Fv-antibodies against SARS-CoV-2 spike protein (SP) were screened from an autodisplayed Fv-antibody library which was expressed on E. coli outer membrane, and the receptor binding domain (RBD) of SP was used as a screening probe. The screened target clones were analyzed to have quantitative binding properties to the RBD, and the Fvantibodies from the screened target clones were expressed as soluble proteins. The binding affinity (KD) of expressed Fv-antibodies to the RBD was estimated to be 70-85 nM using SPR biosensor. The specific binding properties of Fv-antibodies were analyzed for pseudo-virus particles with SARS-CoV-2 SP on the Lenti-virus envelope, such as wild type (Wuhan-1) and variants (Delta, Omicron BA.2, Omicron BA.4/5) using a SPR biosensor. The detection of real SARS-CoV-2 (Wild type, Wuhan-1) based on a SPR biosensor was also presented using the Fv-antibodies with the binding constant (KD) of cycle threshold value (Ct) = 33.8-32.9 (2.19-4.08 copies/mu L) and LOD of 0.67-0.83 copies/mu L (Ct = 35.5-35.2). Finally, one-step immunoassay based on switching peptide was demonstrated for the detection of the real SARS-CoV-2 (Wuhan-1) without any washing step. The binding constant (KD) was estimated to be Ct = 35.2-33.9 (0.83-2.04 copies/mu L), and LOD was estimated to be 0.14-0.47 copies/mu L (Ct = 37.8-36.0). Considering the LOD of the conventional RT-PCR (Ct = 35), the LOD of the one-step immunoassay based on the switching peptide was determined to be feasible for the medical diagnosis of COVID-19.